The Influence of Self-Efficacy, Entrepreneurial Knowledge and Entrepreneurial Motivation on Entrepreneurial Interest - Saryadi Saryadi; Liss Dyah Dewi Arini; Bangun Prajadi Cipto Utomo (International Journal of Contemporary Sciences (IJCS), 2024)
This study is to understand the influence of self-efficacy, entrepreneurial knowledge and Entrepreneurial motivation on student interest in entrepreneurship at the Faculty of Health Sciences UDB Surakarta, with respondents totaling 103 students with the distribution of google forms. Data were obtained cross-sectionally. Testing with questionnaire test. Data analysis used multiple linear regression, partial test and together, coefficient of determination. The results showed individually and together illustrate the significant positive influence of self-efficacy, entrepreneurial knowledge and Entrepreneurial motivation on entrepreneurial interest. Studies show that entrepreneurial knowledge, self-efficacy, and motivation influence entrepreneurial interest significantly. Entrepreneurial knowledge, motivation and self-efficacy could affect 85.8 percent, with other variables not included in the research model affecting 14.2 percent